THE DAUGHTERS OF MEN AND THE SONS OF GOD: THE FALL OF THE ANGELS AND THE (NON)VEILING OF THE WOMEN ACCORDING TO TERTULLIAN (Annual of the Faculty of Philosophy in Skopje, 2024)
Тhe text outlines Tertullian’s stances on the catastrophic unification (by way ofmarriage) of the daughters of men with the sons of God from the story about the fallenangels. The offspring produced by this merger is horrifically dangerous to the humanrace on earth, and therefore, Tertullian’s aim is to prevent any sort of reactualizationof such a disastrous event. He communicates this through his positions on the primordialsinfulness of the woman, and the blame cast onto the beautiful daughters of men,who, with their unhumble and uncovered beauty tempted the angels so strongly, thatthey caused them to abandon their celestial abodes and functions, and descend to earth,thus disrupting the order in the world, and bringing people problematic knowledge andvarious problematic capabilities, of which the еvilest were those most appealing to thewomen.Tertullian’s aim is to insist on the necessity of the covering of women, especiallyvirgins, since those were the errant daughters of men from the story, so that they do notpose a danger to the chastity of men, and more importantly, to the innocence, moralityand the ontological stability of the angels, and with this, the structure and functioningof the religious community. These objectives are overviewed through his polemic withMarcion, and through his strong opposition to the customs of uncovering by a part ofthe women within the church(es). Through chosen examples from Tertullian’s opus,the instances in which he mentions the motif of the fallen angels through the blame andsin of the daughters of men, and the need to prevent any such transgression are shown.
Keywords: Tertullian; fallen angels; virgins; women; veiling